Ameliorasi dan pemupukan fosfat alam pada tanah gambut dan serapan p oleh tanaman jagung=Amelioration and Rock Phosphate Fertilization in Peat Soil - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
, In the, soil acidity, the P element has a great role in the increasing of plant growth and yield. Based on these explanations, this research was done to increase the productivity of peat soil by increasing the available P with amelioration and addition of phosphate rock for maize. This research was done in the green-house and the laboratorium of Soil Science Department of Agricultural Faculty of UGM, Ygyakarta. This experiment used peat soil of Rengat of Riau province from 0 to 30 cm. It used split plot design and three replications, without ameliorant, lime, oil palm bunch ash and volcanic ash as main plot. Ameliorant were added at the rate of 10 and 20 ton/ha. The rock phosphate consisted of 0, 100, 200 and 300 kg P20,/ha as the sub plot. The Urea and KCl were given as a basic fertilizer and the dosage of each were 300 kg/ha and 150 kg/ha. The result of this research showed that the oil palm bunch ash could increase pH, P uptake by shoot and root, Ca and Mg by root, and growth of plant, it also increased the pH, residual available-15, total P, K, Ca and Mg of peat soil after experiment. Lime increased the pH and total Ca of the peat soil after the experiment. Volcanic ash increased Ca uptake by shoot and root, Mg by shoot and growth of plant. The highest P uptake and growth was found on 10 ton/ha oil palm bunch ash wihout phosphate rock. The addition of 20 ton/ha of oil palm bunch ash and volcanic ash of 10 and 20 ton/ha must be followed-with the addition of 200 to 300 kg P20 /ha of rock phosphate in order to find the best growth of plant and the highest nutrient uptake.